2021
DOI: 10.1016/j.sdentj.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between diabetes mellitus and number of restored, carious lesions and missing teeth: A retrospective radiographic evaluation

Abstract: Aim This study aimed to evaluate the prevalence of carious, restored, and missing teeth among diabetic and non-diabetic patients who visited dental clinics in Dammam, Saudi Arabia. Method This retrospective study was conducted between April and November 2018. The data collection procedure was conducted in two steps: (1) review of patient records for the demographic variables and (2) screening of digital panoramic radiographs (OPGs). The patients who visited the restorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…As per WHO recommendation, the present study analysed 13 teeth as a minimum of twenty functional teeth are required for good oral health, 5 although it is not a consensus among similar studies. 5,7,8,25 A synergistic effect on increasing tooth loss 11,13 of those studied non-communicable chronic diseases has increased prevalence in recent decades 13,26,27 and those may have low oral health index from caries or periodontal disease, having a multifactorial origin, lead to tooth loss. 8,20,28 However, in our age-stratified analysis, only CVD was statistically associated with 13 or more teeth loss in the 65 years and older group (1.10: 95% CI: 1.05-1.15) in the 2019 analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As per WHO recommendation, the present study analysed 13 teeth as a minimum of twenty functional teeth are required for good oral health, 5 although it is not a consensus among similar studies. 5,7,8,25 A synergistic effect on increasing tooth loss 11,13 of those studied non-communicable chronic diseases has increased prevalence in recent decades 13,26,27 and those may have low oral health index from caries or periodontal disease, having a multifactorial origin, lead to tooth loss. 8,20,28 However, in our age-stratified analysis, only CVD was statistically associated with 13 or more teeth loss in the 65 years and older group (1.10: 95% CI: 1.05-1.15) in the 2019 analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The following adjustment variables were considered because they are related to both exposures and outcome as confounders 2,[5][6][7][8][9]11,16,[20][21][22][23] : Gender (male/female); Current level of education (complete higher education, complete secondary education, complete primary education and incomplete primary education or less); Age (categorical in the descriptive analysis, being 18-34, 35-44, 45-54, 55-64 and >65 years old, and continuous in years in the multivariate analysis); Macro region of Brazil (since Brazil has continental dimensions: Southeast, South, Midwest, Northeast or North); Region (urban/rural); Smoking (no/yes); and Abusive alcohol consumption (no/yes). It was considered abusive to consume five or more doses for men and four or more doses for women, on a single occasion, in the last 30 days.…”
Section: Covariatesmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Data from several reports suggest that people with diabetes are at high risk of periodontal disease and tooth loss. [7][8][9] Previous research has not reported delayed wound healing and increased postoperative infections after tooth extraction. [10][11][12][13] Although there exists a systematic review on the management of tooth extraction in diabetic patients, there is a paucity of literature on the outcomes of tooth extraction in people with diabetes.…”
Section: Introductionmentioning
confidence: 99%